Basal forebrain magnocellular cholinergic systems are damaged in mice following neonatal hypoxia‐ischemia. Issue 8 (3rd November 2021) - Northington, Frances J.; Kratimenos, Panagiotis; Turnbill, Victoria; Flock, Debra L.; Asafu‐Adjaye, Daniella; Chavez‐Valdez, Raul; Martin, Lee J.
Abstract: Neonatal hypoxic‐ischemic encephalopathy (HIE) causes lifelong neurologic disability. Despite the use of therapeutic hypothermia, memory deficits and executive functions remain severely affected. Cholinergic neurotransmission from the basal forebrain to neocortex and hippocampus is central to higher cortical functions. We examined the basal forebrain by light microscopy and reported loss of choline acetyltransferase‐positive (ChAT)+ neurons, at postnatal day (P) 40, in the ipsilateral medial septal nucleus (MSN) after neonatal hypoxia‐ischemia (HI) in mice. There was no loss of ChAT+ neurons in the ipsilateral nucleus basalis of Meynert (nbM) and striatum. Ipsilateral striatal and nbM ChAT+ neurons were abnormal with altered immunoreactivity for ChAT, shrunken and crenated somas, and dysmorphic appearing dendrites. Using confocal images with 3D reconstruction, nbM ChAT+ dendrites in HI mice were shorter than sham ( p = .0001). Loss of ChAT+ neurons in the MSN directly correlated with loss of ipsilateral hippocampal area. In the nbM and striatum, percentage of abnormal ChAT+ neurons correlated with loss of ipsilateral cerebral cortical and striatal area, respectively. Acetylcholinesterase (AChE) activity increased in adjacent ipsilateral cerebral cortex and hippocampus and the increase was linearly related to loss of cortical and hippocampal area. Numbers and size of cathepsin D+ lysosomes increased in large neurons in the ipsilateral nbM. After neonatal HI, abnormalities were found throughout the major cholinergic systems in relationship to amount of forebrain area loss. There was also an upregulation of cathepsin D+ particles within the nbM. Cholinergic neuropathology may underlie the permanent dysfunction in learning, memory, and executive function after neonatal brain injury. Abstract : Mouse cholinergic systems: Poor executive function and decreases in memory and learning are seen after neonatal HIE. We examined the cholinergic systems to determine if there is pathology there that could contribute to these functional outcomes. In contrast to normal, after neonatal HI on P10, loss of permanent attrition of ChAT neurons in the MSN, nbM, and striatum is found. ChAT+ neurons are crenated with shorter dystrophic dendrites. Increased and larger lysosomes are also present in the nbM. Within the injured ipsilateral cortex, AChE activity is abnormally increased. We hypothesize that permanent injury to the cholinergic systems after neonatal HI is responsible for these poor neurologic outcomes.